Parenting and children's adjustment problems: the mediating role of self-esteem and peer relations. Issue 4 (1st October 2016) - Georgiou, Nicos A.; Stavrinides, Panayiotis; Georgiou, Stelios
ABSTRACT: The aim of this study was to investigate the impact of parental and personal characteristics on children's internalizing/externalizing problems. Further, this study aimed to examine personal characteristics (self-esteem, peer relations) as mediators in the relation between parenting and internalizing/externalizing problems. In order to address these questions, this study used a cross-sectional design. The sample included 588 pre-adolescents and adolescents (10–14 years old) and their mothers. Children completed the My Memories of Upbringing Questionnaire, the Strengths and Difficulties Questionnaire (child report), the Rosenberg Self-Esteem Scale, the Friendship Quality Questionnaire, and the Harter's Self Perception Profile (Social acceptance subscale), while mothers completed The Strengths and Difficulties Questionnaire (parent report). Results support a model for the influence of both direct and indirect effects on children's internalizing/externalizing problems.